MLTI-19. VENOUS THROMBOEMBOLIC EVENTS IN PATIENTS WITH BRAIN METASTASES: THE PICOS SCORE. (12th August 2019) - Wolpert, Fabian; Grossenbacher, Bettina; Lareida, Anna; Roth, Patrick; Neidert, Marian; Andratschke, Nicolaus; Le Rhun, Emilie; Weller, Michael
Abstract: BACKGROUND: Venous thromboembolic events are significant complications in patients and possibly associated with an unfavorable outcome. Thrombosis risk is poorly defined for patients with brain metastasis, and available risk calculation scores are not validated for these patients. METHODS: We identified 811 patients with brain metastasis followed at our institution and screened electronic charts retrospectively for the occurrence of venous thromboembolic events, along with candidate risk factors. Risk factors were tested in uni- and multivariate analyses and finally integrated in a score model for risk prediction. RESULTS: Venous thromboembolic events were documented in 97 of 811 patients (12.0%). Primary tumors with high thrombogenicity (p=0.02, odds ratio 1.7, 95% CI 1.1–2.8), dexamethasone (p=0.011, odds ratio 2.27, 95% CI 1.5–4.5), chemotherapy (p=0.005, odds ratio 3.4, 95% CI 1.6–7.5), BMI > 35 kg/m 2 (p=0.002, odds ratio 3.4, 95% CI 1.6–7.5) and immobilization (p=0.003, odds ratio 2.4, 95% CI 1.3–4.3) were confirmed as independent predictors of VTE. We derived a score model for venous thromboembolic event prediction, the PICOS (thrombogenic P rimary, I mmobilization, C hemotherapy, O besity, S teroids) score (0–7 points). Receiver Operating Characteristic Curve Analysis demonstrated its prognostic accuracy (AUC=0.71, 95% CI 0.64–0.77), and its predictive capability was superior to that of other scores proposed for the evaluation of venous thromboembolic event risk such as the Khorana (AUC=0.51) or CONKO (AUC=0.52) scores. CONCLUSIONS: We report a rate of venous thrombotic events of 12.0% in our cohort of 811 patients with brain metastasis. We define a risk model for prediction in of venous thrombotic events in patients with BM, the PICOS score. It may become a valuable tool for the identification of brain metastasis patients at high risk for venous thromboembolic events and be helpful for guidance of clinicians towards decision whether to start thrombosis prophylaxis. Further, the PICOS score might be used for stratification in controlled studies.